On-chip detection of a single nucleotide polymorphism without polymerase amplification - Han, Jinhee (Nano Res, 2014)
A nanoparticle-assembled photonic crystal (PC) array was used to detect single nucleotide polymorphism (SNP). The assay platform with PC nanostructure enhanced the fluorescent signal from nanoparticle-hybridized DNA complexes due to phase matching of excitation and emission. Nanoparticles coupled with probe DNA were trapped into nanowells in an array by using an electrophoretic particle entrapment system. The PC/DNA assay platform was able to identify a 1 base pair (bp) difference in synthesized nucleotide sequences that mimicked the mutation seen in a feline model of human autosomal dominant polycystic kidney disease (PKD) with a sensitivity of 0.9 fg/mL (50 aM)-sensitivity, which corresponds to 30 oligos/array. The reliability of the PC/DNA assay platform to detect SNP in a real sample was demonstrated by using genomic DNA (gDNA) extracted from the urine and blood of two PKD(−) wild type and three PKD positive cats. The standard curves for PKD positive (PKD(+)) and negative (PKD(−)) DNA were created using two feline-urine samples. An additional three urine samples were analyzed in a similar fashion and showed satisfactory agreement with the standard curve, confirming the presence of the mutation in affected urine. The limit of detection (LOD) was 0.005 ng/mL which corresponds to 6 fg per array for gDNA in urine and blood. The PC system demonstrated the ability to detect a number of genome equivalents for the PKD SNP that was very similar to the results reported with real time polymerase chain reaction (PCR). The favorable comparison with quantitative PCR suggests that the PC technology may find application well beyond the detection of the PKD SNP, into areas where a simple, cheap and portable nucleic acid analysis is desirable.